Specific Characteristics of English Education in Technical Universities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article deals with the specific characteristics of English education in technical universities, highlighting the unique challenges and methodologies involved in teaching English to students pursuing technical disciplines. The increasing global interconnectedness necessitates a strong command of the English language for professionals in engineering, technology, and applied sciences. The study examines the integration of technical vocabulary, communication skills, and specialized content into English language curricula. Furthermore, it discusses the impact of modern instructional methodologies, including task-based learning and the use of technology in the classroom, on enhancing students' language proficiency and professional readiness. By addressing the needs and interests of technical students, this article provides insights into effective pedagogical strategies for improving English language education in technical institutions.